OPENFOAM 3D Modeling of Melt Spinning Process in Non-planar Geometry - Maroni, Adrian Gaston (2018)
Melt spinning is an industrial process used for the production of metallic glasses. It is a rapid solidification process whereby a liquid metal is ejected at high pressure and temperature via a nozzle onto a rotating copper wheel by solidifying in the form of a thin ribbon. In this work, we perform a 3D simulation model to reproduce the melt spinning process to get amorphous magnetic material, starting from an alloy with chemical composition Fe75Si10B15(% at.). A CFD model in the OpenFoam® open source code is proposed and applied, which is based on the Finite Volume Method (FVM) and Volume of Fluid Method (VOF). The entire process without solidification is analyzed simply as a preliminary study of the ejection conditions during the melt, in order to avoid posterior turbulence in the film that would cause irregularities in subsequent stages of solidification. This preliminary analysis aims to study the generation of a regular film of molten material on a rotating cylindrical geometry. In the FVM method the coupled incompressible laminar momentum and continuity equations are solved at each time step on every mesh cell, while in the VOF scheme the fluid properties are weighed average of those of air and molten metal. The complete geometry is discretized in a block-structured mesh of pure hexahedra. The profile and dimensions of the resulting meniscus and ribbon during the transient are in good agreement with our previous numerical results.